DETERMINATIVE METHODS OF OPTIMIZATION OF GAS TRANSPORT SYSTEMS OPERATING MODES - Грудз, Володимир Ярославович; Грудз (молодший), Володимир Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Methods of creating mathematical models of technological processes of gas transportation by systems of main gas pipelines are considered, characteristics of principles of modelling of stationary and non-stationary processes are given.